A recent L1 insertion within SPEF2 gene is associated with changes in PRLR expression in sow reproductive organs. (9th April 2014) - Sironen, A.; Fischer, D.; Laiho, A.; Gyenesei, A.; Vilkki, J.
Summary The immotile short tail sperm (ISTS) defect was recognized in the Finnish Yorkshire population at the end of the 1990s when several affected boars were identified. The causal mutation for this defect is a recent L1 insertion within the SPEF2 gene. In 2001, the insertion frequency was already 0.23. Even though all homozygous boars are eliminated from the population due to infertility, the amount of affected boars increased rapidly until marker‐assisted selection against the defect was established. Previously we identified an association between the L1 insertion and litter size in the first parity. In this study, we analyzed the expression of the genomic region adjacent to the L1 insertion on porcine chromosome 16. Based on the RNA‐seq data analysis, prolactin receptor (PRLR) was identified as down‐regulated in the oviduct of ISTS homozygous sows. Quantitative PCR (qPCR) analysis confirmed the significant down‐regulation of PRLR in the ovary, oviduct, and uterus of ISTS homozygous and carrier sows compared with controls. In addition, three unannotated loci between PRLR and SPEF2 showed some transcription activity in the analyzed samples. We further investigated the possible mechanisms of the L1 influence on the decrease in the identified gene expression. The methylation pattern of the PRLR gene region appeared unaffected. However, reads mapping to the L1 sequence indicated an increase in L1 antisense promoter expression in the ISTS homozygous animals. The current data suggest that the presence of the L1 affects by some mechanism the expression patterns upstream of the insertion site.